Female pseudohermaphroditism: Congenital adrenal hyperplasia presenting with diffuse hyperpigmentation - Saeed, Wajieha; Butt, Ghazala; Khurshid, Khawar (Journal of Pakistan Association of Dermatologists, 2018)
The term congenital adrenal hyperplasia (CAH) comprises a group of autosomal recessive disorders, each of which involves a deficiency of an enzyme involved in the synthesis of cortisol, aldosterone, or both. The clinical presentation varies according to chromosomal sex. The sex of neonate with CAH is often initially unclear because of genital ambiguity. We report a case of 25-year-old phenotypically male, presenting with generalized hyperpigmentation for 5 years and occasional syncope for 1 year. On examination there were sparse axillary and pubic hair with ambiguous genitalia. 46XX karyotype, hypoplastic uterus on CT scan and elevated ACTH and 17-hydroxyprogesterone levels lead to the diagnosis of female pseudohermaphroditism due to congenital adrenal hyperplasia and patient was started on glucocorticoids and fludrocortisone by endocrinologist and was also referred to plastic surgeon.